2020
DOI: 10.1039/d0ja00112k
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental analysis of vegetable oils and fats by means of ICP-OES following a dilution and shot methodology

Abstract: The accurate direct elemental analysis of fats and oils is accomplished according to a dilution and shot analysis method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Olive oil is a high-viscosity lipid matrix. Its viscosity makes analysis with spectrometric instruments challenging [ 53 ]. Due to the critically low concentrations of some elements in olive oil, the latest studies tended to promote the use of ICP-MS known for its high sensitivity.…”
Section: Olive Oil Geographical Authentication By Means Of Trace Elem...mentioning
confidence: 99%
See 2 more Smart Citations
“…Olive oil is a high-viscosity lipid matrix. Its viscosity makes analysis with spectrometric instruments challenging [ 53 ]. Due to the critically low concentrations of some elements in olive oil, the latest studies tended to promote the use of ICP-MS known for its high sensitivity.…”
Section: Olive Oil Geographical Authentication By Means Of Trace Elem...mentioning
confidence: 99%
“…( Figure 4 ). They are often designed to obtain a final solution that can be rapidly and easily analysed using various spectrometric instruments [ 53 , 58 ].…”
Section: Olive Oil Geographical Authentication By Means Of Trace Elem...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in agreement with those previously shown for other complex matrices. 23 Moreover, the impact of the temperature on sensitivity was also evaluated. It was observed that the sensitivity increased with the hTISIS temperature, peaking at 300-400 C. Above these temperatures, a drop in sensitivity was observed.…”
Section: Inuence Of Htisis Temperaturementioning
confidence: 99%
“…Therefore, a universal calibration procedure can be implemented in which external calibration with a set of xylene-based standards can be used for the analysis of all kind of organic samples. 23 However, the increase in the spray chamber wall temperature leads to an increase in the amount of solvent reaching the plasma, thus causing plasma degradation or soot deposits. A possible solution to lower the amount of solvent delivered to the plasma is to introduce the sample according to an airsegmented injection procedure, thus obtaining transient signals.…”
Section: Introductionmentioning
confidence: 99%